KOMBINASI BISNIS BANK SYARIAH: REFLEKSI SATU TAHUN BANK SYARIAH INDONESIA - Su'ud Wahedi (Al-Idarah, 2022)
This research aims to explore the achievement of PT Bank Syariah Indonesia (BSI) in the first year implemented business combination. Data are penetrated from several information and quarterly financial statements that published through website of BSI. The results of this research show that business combination that executed by BSI is a merger where a company that become a survivor is PT BRI Syariah, Tbk., while Bank Syariah Mandiri and BNI Syariah become merging companies. So, BSI is a subsidiary company of PT Bank Rakyat Indonesia, Tbk. The products and services that offered by BSI to its customers are multi-enough and also accommodate the needs of customers both have sophisticate and naive of technology. Beside of that, the financial performance of BSI also works out positively trend during three quarters respectively. The limitations of this research are only to capture operationally one year of BSI and just take three aspects namely portion of ownership, products & services and financial performance, so relatively lack to show the comprehensive condition. The suggestion for next research is to develop or take other aspects that not studied in this research.